Exponential acceleration to improve Simpson’s 3/8-rule - alkilaby, salah; Adil AL_Rammahi (Al-Qadisiyah Journal of Pure Science, 2020)
in this paper we present a developed method for improving the results of numerical integration by using accelerations on the Simpson rule 3/8 to obtain better results and about twice faster than this rule. It is very useful to reduce the error rate and facilitate access to more accurate results.